Application of remote monitoring and combined network platforms in the management of pulmonary dysfunction patients in the Department of Spinal Surgery (远程监测与联合网络平台在脊柱外科肺功能不全患者管理中的应用) - HUANG Xiaoyan (黄晓妍); TAN Xiaoju (谭晓菊) (中西医结合护理)
Objective To investigate the effect of remote monitoring and combined network platforms in the management of patients with pulmonary dysfunction in in the Department of Spinal Surgery. Methods This study used a randomized controlled trial method to conduct continuous case screening on patients who visited the Spinal Surgery Department from January 2019 to December 2023. Among them, 46 patients with pulmonary dysfunction were selected for the study, and randomly divided into a control group and an experimental group, with 23 cases in each group. The control group was given routine management including medication therapy, respiratory therapy, physical therapy, psychological support, and lung function monitoring. The remote monitoring and combined network platform management were adopted in the experimental group, and it consisted of evaluation and registration, equipment configuration and training, data monitoring, data analysis, education and support, appointment reminders, and follow-up services. Both groups were intervened for six months, and the lung function indicators (FEV1, FEV1/FVC, and PEF) and quality of life scores were compared before and after the intervention. Results After intervention, both groups showed improvement in lung function, and the FEV1, FEV1/FVC, and PEF in the experimental group were all higher than those in the control group(P＜0. 05). The experimental group had higher scores in physical strength, medical care, daily life, social psychology, work, and medical conditions than the reference group, and the differences between the groups were statistically significant(P＜0. 05). Conclusion In the management of pulmonary dysfunction patients undergoing spinal surgery, remote monitoring and combined network platforms are effective in promoting the recovery of patients' pulmonary function and improving their quality of life. (目的 分析远程监测与联合网络平台在脊柱外科肺功能不全患者管理中的应用效果。方法 采用随机对照试验方法, 对医院脊柱外科2019年1月—2023年12月期间就诊的患者进行连续病例筛查, 从中选取46例肺功能不全患者进行研究。随机分为对照组与试验组, 各23例。对照组给予常规管理, 包括药物治疗、呼吸治疗、物理治疗、心理支持以及肺功能监测等; 试验组基于远程监测联合网络平台开展管理, 包括评估与注册、设备配置与培训、数据监测、数据分析、教育与支持、预约提醒与随访服务。两组均干预半年。对比两组干预前和干预后肺功能指标第1秒用力呼气量(FEV1)、第1秒用力呼气量占用力肺活量比值(FEV1/FVC)、呼气峰流量(PEF), 采用中国心血管病人生活质量评定问卷(CQQC)评估患者生活质量。结果 干预后, 两组肺功能均改善, 且试验组FEV1、FEV1/FVC以及PEF均高于对照组, 差异有统计学意义(P＜0. 05)。试验组CQQC量表体力、医疗状况、一般生活、社会心理状况、工作状况以及病情得分均高于对照组, 差异有统计学意义(P＜0. 05)。结论 在脊柱外科肺功能不全患者管理中, 远程监测与联合网络平台更有效地促进患者肺功能恢复, 提高患者生活质量。)